2011
DOI: 10.1111/j.1540-6229.2010.00296.x
|View full text |Cite
|
Sign up to set email alerts
|

The Walkability Premium in Commercial Real Estate Investments

Abstract: This article examines the effects of walkability on property values and investment returns. Walkability is the degree to which an area within walking distance of a property encourages walking for recreational or functional purposes. We use data from the National Council of Real Estate Investment Fiduciaries and Walk Score to examine the effects of walkability on the market value and investment returns of more than 4,200 office, apartment, retail and industrial properties from 2001 to 2008 in the United States.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
4
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(139 citation statements)
references
References 72 publications
(65 reference statements)
10
117
4
8
Order By: Relevance
“…For the relationship between commercial activities and residential property values, urban economic theory provides two explanations [1,2]. On the one hand, the ease of access to commercial services has a positive impact on residential property value by promoting convenience and reducing travel costs.…”
Section: Introductionmentioning
confidence: 99%
“…For the relationship between commercial activities and residential property values, urban economic theory provides two explanations [1,2]. On the one hand, the ease of access to commercial services has a positive impact on residential property value by promoting convenience and reducing travel costs.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Matthews and Turnbull (2007) showed that a more grid-like street pattern increased property values in more pedestrian-oriented neighborhoods and decreased property values in automobile-oriented neighborhoods. Other work finds that each incremental increase in walk ability, using walk score as a metric, can be associated an increase in property values of up to 9% [43].…”
Section: Walk Ability Economic Value and Demandmentioning
confidence: 99%
“…Walkscore.com calculates an area's walk score based on the ease of being able to walk to amenities such as restaurants and libraries. Though this measure is just beginning to be included in quantitative studies, it is consistently found to have a positive relationship with real estate values (see, e.g., Kok & Jennen, 2012;Pivo & Fisher, 2011;Rauterkus & Miller, 2011). Krause and Bitter (2012) predict that it will become widely adopted in the real estate valuation literature in the near future.…”
Section: Environmentmentioning
confidence: 99%